Prognostic significance of brain temperature and intracranial pressure in patients with acute brain injury. - XU, Wei; XIA, Jing; SHI, Yi; ZHANG, Ming; HAN, Bing-sha; FENG, Guang; WANG, Chun-lin (Chinese Journal of Contemporary Neurology & Neurosurgery, 2026)
Objective To explore the predictive value of brain temperature (BT) and intracranial pressure (ICP) for prognosis in patients with acute brain injury. Methods Fifty patients with acute brain injury admitted to He'nan Provincial People's Hospital and The 901st Hospital of Joint Logistics Support Force from March 2024 to June 2025 were included. BT and ICP were continuously and dynamically monitored for 5-7 d. Poor prognosis was defined as a Glasgow Outcome Scale-Extended (GOS-E) score < 4, and good prognosis as a GOS-E score ≥ 4 at 90-day after discharge. Univariate and multivariate Logistic regression analyses were used to screen for risk factors of prognosis. Receiver operating characteristic (ROC) curve was drawn to determine the optimal cut-off value of BT and ICP. Based on this, BT and ICP were divided into low-value group and high-value group. Kaplan-Meier curve was drawn, and univariate and multivariate Cox proportional hazards regression models were used to analyze risk factors for 90-day survival after discharge. Results The BT (P = 0.000) and ICP (P = 0.000) in good prognosis group (n = 27) were lower than those in poor prognosis group (n = 23). Logistic regression analysis showed that increased BT (OR = 6.145, 95%CI: 1.569-24.063; P = 0.009) and ICP (OR = 1.827, 95%CI: 1.200-2.780; P = 0.005) were risk factors for poor prognosis in patients with acute brain injury. The ROC curve showed that the area under the curve (AUC) for predicting poor prognosis by BT and ICP was 0.833 (95%CI: 0.719-0.946, P = 0.000) and 0.860 (95%CI: 0.737-0.961, P = 0.000), respectively, with the optimal cut-off values being 37.8 °C and 17 mm Hg. The 90-day after discharge survival rate was 58% (29/50). Kaplan-Meier survival analysis showed that the survival rate of patients with high BT (≥ 37.8 °C) was lower than that with low BT (< 37.8 °C; HR = 5.240, 95%CI: 1.938-14.169, P = 0.001), with high ICP (≥ 17 mm Hg) was also lower than that with low ICP (< 17 mm Hg; HR = 3.104, 95%CI: 1.373-7.021, P = 0.007). The survival rate of the low BT + ICP group remained at a relatively high level, with the best prognosis among 4 groups. Only 2 groups (high BT group and high ICP group) showed an increase in a single indicator, and the survival rate was between the low BT + ICP group and the high BT + ICP group. Multivariate Cox proportional hazards regression analysis showed that patients with BT ≥ 37.8 °C (HR = 4.561, 95%CI: 1.615-12.879; P = 0.004) and ICP ≥ 17 mm Hg (HR = 2.995, 95%CI: 1.283-6.807; P = 0.011) had a higher risk of death. Conclusions BT and ICP have a good predictive value for the prognosis of patients with acute brain injury, and can be used as an effective tool for clinical risk stratification.